2017
DOI: 10.1007/s10120-017-0718-5
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline-based triplets do not improve the efficacy of platinum-fluoropyrimidine doublets in first-line treatment of advanced gastric cancer: real-world data from the AGAMEMON National Cancer Registry

Abstract: Background Although anthracycline-based triplets are one of the most widely used schedules to treat advanced gastric cancer (AGC), the benefit of including epirubicin in these therapeutic combinations remains unknown. This study aims to evaluate both the efficacy and tolerance of triplets with epirubicin vs. doublets with platinum-fluoropyrimidine in a national AGC registry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
2
14
1
Order By: Relevance
“…The use of an unusual treatment regimen may limit opportunities for second-line treatment and subsequent OS benefit. [4][5][6]14 In our study, we found less serious (grade 3-5) toxicity in patients receiving doublets (21%) compared to triplets (33%) as well as similar OS and TTF rates, which supports the shift toward doublet therapy as preferred strategy in these patients. Current national and international guidelines recommend a fluoropyrimidine and platinum doublet in metastatic esophagogastric cancer patients, with the addition of an anthracycline or taxane in selected patients.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…The use of an unusual treatment regimen may limit opportunities for second-line treatment and subsequent OS benefit. [4][5][6]14 In our study, we found less serious (grade 3-5) toxicity in patients receiving doublets (21%) compared to triplets (33%) as well as similar OS and TTF rates, which supports the shift toward doublet therapy as preferred strategy in these patients. Current national and international guidelines recommend a fluoropyrimidine and platinum doublet in metastatic esophagogastric cancer patients, with the addition of an anthracycline or taxane in selected patients.…”
Section: Discussionsupporting
confidence: 67%
“…25,26 Since the added value of the addition of an anthracycline to a platinum-fluoropyrimidine doublet remains uncertain, 15,[27][28][29] doublet chemotherapy tends to be the favored choice of firstline palliative treatment because of its better tolerance. [4][5][6]14 In our study, we found less serious (grade 3-5) toxicity in patients receiving doublets (21%) compared to triplets (33%) as well as similar OS and TTF rates, which supports the shift toward doublet therapy as preferred strategy in these patients.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Patients are from the AGAMENON database, a national registry of consecutive cases of AGC, in which 30 Spanish centers and one Chilean center have participated. The study design, characteristics, method, and data quality criteria have been widely communicated elsewhere (9)(10)(11)(12)(13).AGAMENON is a non-interventionist database sponsored by the investigators themselves. Data are collected by means of a web-based data collection tool (http://www.agamenonstudy.com/).…”
Section: Study Design and Participantsmentioning
confidence: 99%